Unveiling mungbean yellow mosaic virus: molecular insights and infectivity validation in mung bean (Vigna radiata) via infectious clones - Balasubramaniam, Madhumitha; Thangavel, Tamilnayagan; Aiyanathan, Karupiah Eraivan Arutkani; Rathnasamy, Sakthi Ambothi; Rajagopalan, Veera Ranjani; Subbarayalu, Mohankumar; Natesan, Senthil; Kanagarajan, Selvaraju; Muthurajan, Raveendran; Manickam, Sudha (Frontiers in Plant Science, 2024)
Yellow mosaic disease with typical symptoms of alternate bright yellow to green patches associated with stunting, downward cupping and wrinkling was observed on mung bean in the agricultural farms at Coimbatore, Tamil Nadu, India. PCR using gene-specific primers indicates the presence of yellow mosaic virus in the symptomatic plants. Rolling circle amplification (RCA) followed by restriction digestion detected 2.7 kb of DNA-A and DNA-B, revealing the identification of a bipartite genome. The full-length genome sequences were deposited in NCBI GenBank with the accession numbers MK317961 (DNA-A) and MK317962 (DNA-B). Sequence analysis of DNA-A showed the highest sequence identity of 98.39 % with DNA-A of MYMV-Vigna radiata (MW736047), and DNA-B exhibited the highest level of identity (98.21 %) with MYMV-Vigna aconitifolia isolate (DQ865203) reported from Tamil Nadu. Recombinant analysis revealed distinct evidence of recombinant breakpoints of DNA-A within the region coding for ORF AC2 (transcription activation protein) with the major parent identified as MYMV-PA1 (KC9111717) and the potential minor parent MYMV-Namakkal (DQ86520.1). Interestingly, a recombination event in the CR region of DNA-B, which codes for nuclear shuttle protein and movement protein, was detected. MYMIV-M120 (FM202447) and MYMV-Vigna (AJ132574) have been identified as the event's major and minor parents, respectively. This large variation in DNA-B led us to suspect a recombination in DNA-B. Dimeric MYMV infectious clones were constructed, and the infectivity was confirmed through agroinoculation. In future prospects, unless relying on screening using whiteflies, breeders and plant pathologists can readily use this agroinoculation procedure to identify resistant and susceptible cultivars against YMD.